If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28(3) = x Multiply 28 * 3 84 = x Solving 84 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 84 + -1x = x + -1x Combine like terms: x + -1x = 0 84 + -1x = 0 Add '-84' to each side of the equation. 84 + -84 + -1x = 0 + -84 Combine like terms: 84 + -84 = 0 0 + -1x = 0 + -84 -1x = 0 + -84 Combine like terms: 0 + -84 = -84 -1x = -84 Divide each side by '-1'. x = 84 Simplifying x = 84
| 33+3x=34 | | 9x+2=8x-5 | | 29f-73=420 | | 52-18=x | | (5x-9)(7x+2)= | | 9x-4=5/8 | | 0=0.66x+1 | | 1.2-1.9x=0.5(x+3)-0.3(x+5) | | y=3x+68 | | 67(k+79)=313 | | -2x+11=8 | | 6x=-11x-3 | | f(x)=-0.02x^2+x+5.75 | | 7x-11=4x-2 | | 3x+1.5=4.6 | | d/dx((1000)(1.03^x)) | | 175(330-x)+90x=39560 | | 4x^2-y^2+4y-5=0 | | -30=-6g | | -2/3x-4 | | 10x+2=12x+4 | | x=11+4y(-2) | | 1-3(x+8)=-2x-18 | | lne^3x=22 | | (x+(8-3i))(x+(8+3i))=0 | | -5r-29=7(8-4r)+6r | | lne^3x-2=22 | | 5x-5=4x-10 | | 7x-5=3x-6 | | -5(a-8)=5+2a | | 3b-(1+b)=6b+21 | | 2y-(11+4y)=-7 |